2018
DOI: 10.5539/ass.v15n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating English Language Speaking Anxiety among Malaysian Undergraduate Learners

Abstract: Malaysian graduates have a serious lacking in speaking English and this situation has raised an alarming concern in securing employment in the future. Many Malaysian graduates perceive speaking in a foreign language as an intimidating task. This is due to the existence of foreign language anxiety that serves as a hindrance for the undergraduate learners to speak in a foreign language. This study aims to determine the level of speaking anxiety among Malaysian undergraduate learners. The Foreign Language Speakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 14 publications
11
34
1
Order By: Relevance
“…The CLAS results on aspects of communication apprehension, test anxiety and fear of negative evaluation tests indicate that the average score of each aspect is in a moderate position. These results are directly proportional to the findings of other researchers, including Afiqah (2015), Balemir (2009), Miskam andSaidalvi (2019). Although it is at an intermediate level of anxiety, this cannot be juts ignored because it can make a negative contribution to someone who is learning Chinese.…”
Section: Discussionsupporting
confidence: 68%
“…The CLAS results on aspects of communication apprehension, test anxiety and fear of negative evaluation tests indicate that the average score of each aspect is in a moderate position. These results are directly proportional to the findings of other researchers, including Afiqah (2015), Balemir (2009), Miskam andSaidalvi (2019). Although it is at an intermediate level of anxiety, this cannot be juts ignored because it can make a negative contribution to someone who is learning Chinese.…”
Section: Discussionsupporting
confidence: 68%
“…Worde's (2003) study, for example, listed factors causing anxiety as: speaking in front of others, inability to comprehend the target language, fear of negative evaluation, and negative classroom experience. In Miskam and Saidalvi's (2019) study, the factors that caused anxiety among undergraduates were communication apprehension and test anxiety. In Young's (1994) study, teachers judgmental attitude was also another reason for speaking anxiety.…”
Section: Reasons For Speaking Anxietymentioning
confidence: 99%
“…In the Chinese context, Liu (2018) found that both high and low proficiency Chinese university EFL learners experienced speaking anxiety when speaking in English and that both groups employed different types of strategies to manage their anxieties. Miskam and Saidalvi (2019), who conducted a study on English language speaking anxiety among Malaysian undergraduate learners in a public university, also note that whenever students have to give class performance or do public speaking, they experienced high to moderate levels of anxiety. According to Melouah (2013) anxiety originates from a fear of students' inability to obtain their target goal.…”
Section: Introductionmentioning
confidence: 99%
“…The poor indicator of English capability, however high correlation found in language anxiety in Foreign Language proficiency. As in the context of Japan, they are poor in English language and researches found the aspects that reduce language anxiety among the students of universities (Gosiewska, 2018;Masriani et al, 2018;Miskam & Saidalvi, 2019).…”
Section: Horwitz Horwitz and Cope's Theory Of Foreign Language Anxietymentioning
confidence: 99%
“…He further illustrated that "The feeling of tension and nervousness specifically related with second language perspectives, including speaking, listening, reading, writing and learning"-is different from a general feeling of anxiety, and hence, keeps students away from attaining their targets and goals. It suggested in the studies of (Basith et al, 2019;Miskam & Saidalvi, 2019) that the undergraduate suffer speaking anxiety n a majority. This obstacles their learning causing them not to be able to speak fluent in English…”
Section: Introductionmentioning
confidence: 99%